Estimation of Efficiency of Management of Mineral Metabolism Disorders in Children with Rotavirus Infection under the Conditions of Endemic Area - O.M. Gorlenko; N.M. Gema (Zaslavsky O.Yu., 2012)
Due to fundamental research the clinical picture of rotavirus infection, refined individual pathogenesis, therapy and prevention were studied. At the same time, problems of rotavirus infection against iodine deficiency were not brought up almost, and mineral profile wasn't assessed at the time of illness. It is known that the development, demonstration, and the end of any pathologic process are defined by the adequacy and timeliness of the inclusion of the human immune response. But up to the present moment, proper attention was not paid to the question of rotavirus immunogenesis (the study of humoral and cellular immunity, pro- and anti-inflammatory cytokines) in children. Few existing information rather contradictory and remain debatable from a scientific and practical point of view, and need further clarification and analysis. Meanwhile, it is known that more effective treatment and prevention of any disease is possible only when expanding the range of knowledge of its pathogenesis. All the above-mentioned research was a prerequisite for the study of the mineral profile state in children with rotavirus infection under the conditions of endemic area, especially the reaction of cytokines and immune response of patients, which, in our opinion, made it possible to specify and to deepen the knowledge of the pathogenesis of the disease from new positions, to expand opportunities for improving its diagnosis and therapy.